Short Duration Repetitive Transcranial Electrical Stimulation During Sleep Enhances Declarative Memory of Facts - Cellini, Nicola; Shimizu, Renee E.; Connolly, Patrick M.; Armstrong, Diana M.; Hernandez, Lexus T.; Polakiewicz, Anthony G.; Estrada, Rolando; Aguilar-Simon, Mario; Weisend, Michael P.; Mednick, Sara C.; Simons, Stephen B. (Frontiers in Human Neuroscience, 2019)
Transcranial electrical stimulation (tES) during sleep has been shown to successfully modulate memory consolidation. Here we tested the effect of short duration repetitive tES (SDR-tES) during a daytime nap on the consolidation of declarative memory of facts in healthy individuals. We use a previously described approach to deliver the stimulation at regular intervals during non-rapid eye movement sleep, specifically stage NREM2 and NREM3. Similar to previous studies using tES, we find enhanced memory performance compared to sham both after sleep and 48hrs later. We also observed an increase in the proportion of time spent in NREM3 sleep. SDR-tES boosted the duration of slow oscillation (SO) up-states and the overall rate of slow oscillations during NREM2/NREM3 sleep. Change in the SO rate was correlated with greater memory performance 48hrs after the initial learning. Retrospective investigation of brain activity immediately preceding stimulation suggests that increases in the SO rate are more likely when stimulation is delivered during quiescent and asynchronous periods of activity.